Latar Belakang Pendidikan, Pelatihan Dan Jiwa Kewirausahaan Terkait Kinerja Keuangan Ukm (Studi Di Sentra Industri Tenun Ikat Kelurahan Bandar Kidul Kecamatan Mojoroto Kota Kediri) - Martha Hendrati, Ignatia; Muchson, Mochamad (Jurnal Riset Ekonomi dan Bisnis, 2010)
Compared with large enterprises, SMEs are one kind of business that have the best endurance in the face of crisis. This is because the raw material using local raw materials which do not require foreign currency to buy them. Besides, SMEs are flexible in adjusting to economic conditions in crisis or with the needs of the community.The contribution of SMEs to the economy also not be doubted. In 2009 the contribution of SMEs to GDP reached more than 50%, the number of SMEs reached 99% of businesses in addition to large businesses, provide employment for more than 95%. From this data the SME is a business that contributes to economic growth, employment, and reduce poverty.Research results show the R (correlation coefficient) of 0.972, indicating a very strong relationship between free variables and bound variables. The coefficient of determination of 0.945 means that variations in the size of the company's financial performance can be explained by the variation of educational background, training and entrepreneurial spirit and the remaining 94.5% influenced other variables.Keywords : formal education, non formal education, entrepreneur, financial performance, industry centre